Muhasabah Diri dalam Perspektif Hadis - Asmara Wijaya; Repa Hudan Lisalam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Muhasabah is the correction of mistakes, weaknesses, actions, attitudes and similar reviews of oneself. The meaning of self-reflection is a way to cleanse oneself of the mistakes one has made. Apart from that, the way to reflect on yourself is to pray repentance, using the same procedures as prayers in general, you can also pray diligently and make meditation. Muhasabah needs to be made a human need, because it provides many benefits in life in this world and in the afterlife. Muhasabah needs to be done to assess and re-examine what we have done, then improve ourselves. Basically, the meaning of self-muhasabah in Islam is as simple as self-introspection. A process of evaluating yourself for something better.